Rakhsh and Azar Goshasp - mirjalalodin kazazi (Matn/Pizhūhī-i Adabī, 2009)
Horse constitutes an essential part of a hero (Pahlavan) and it seems as a discrete limb to his body. Therefore, the names of famous horses are remembered in the history just as their renowned riders. Among them, Rakhsh, just like its rider Rostam, is a unique creature that was mysteriously picked by Rostam. Rakhsh is a mighty rose quadruped, notoriously flighty and difficult to catch with some legendary and prominent qualities that some have resembled it to fire. In the present research, the relation between Rakhsh and fire, especially Azar Goshasp’s sepand fire, who has been a great warrior, has been studied and analyzed.